Distortions to agricultural incentives: Evidence from Nigerian value chains - Tokgoz, Simla; Allen, Summer L.; Majeed, Fahd; Paris, Bas; Adeola, Olajide; Osabuohien, Evans (John Wiley & Sons, 2020)
Understanding how policies affect price transmission and incentives for producers and consumers along the complete value chain is a relevant research question due to the more globalized structure of agricultural value chains. In particular, Nigerian agricultural value chains have been targeted by a number of policy decisions. We analyze the import‐oriented palm oil value chain and the export‐oriented cacao value chain, estimating the price distortions from policies and their implications for production incentives at the regional level. For palm oil, due to protective trade policies and domestic initiatives, the nominal rate of protection (NRP) at the farmgate for palm oil producers shows that producers have been protected. NRPs at the border for cacao beans and cocoa products are negative, which may be due to a quality gap, the export market structure, and the concentration of buyers in global markets. Negative NRPs at the farmgate are seen for all regions, showing disincentives in the cacao beans export market reverberate through the domestic market despite domestic support policies. In both value chains, NRPs at farmgate vary across regions partially due to regional policy frameworks and partially due to local conditions impacting price transmission.